The protection of traditional medical knowledge by intellectual property law in OAPI - (:unkn) unknown (My University, 2017)
Traditional medical knowledge, which is the aspect of traditional medicine relating to the knowledge of plant-based therapy and which goes from collecting plants to issuing a finished product, is a key component for providing health care coverage for all. According to the World Health Organization (WHO), traditional medical knowledge contributes about 80% of primary health care in Africa. Traditional medical knowledge is perceived as a valuable source of information useful to eradicate African endemic diseases. The WHO and the African Union (AU) consider that traditional medical knowledge is a serious way for researchers to develop new and affordable drugs. Traditional medicinal knowledge is also important for the drug industry where it represents 30% of the researches made in the pharmaceutical sector and constitutes the main source of information in the herbal medicine sector. The drug industry’s increasing interest for traditional medical and the huge media coverage for biopiracy cases strengthened the (scientific, economic, social and politic) value of traditional medicinal knowledge and contribute to justify their protection. However contrary to the current trend in many African countries, it appears that the African Intellectual Property Organization (OAPI) and the Bangui Agreement, does not provide any suitable legal protective mechanism for the intellectual property rights of the holders of traditional medical knowledge (traditional healers, families, indigenous and local communities).In view of the limits and weaknesses of the intellectual property mechanisms to provide an effective protection to traditional medicinal knowledge’s holders, it is quite legitimate to question the legal mechanism or system to implement. In other words, what type of sui generis protection OAPI members can enact to protect traditional medicinal knowledge? This is the question that the present study intends to answer. The aim is to demonstrate from a prospective
Keywords: African Research